Characteristics of Traumatic Urogenital Injuries in Emergency Department; a 10-year Cross-sectional Study - Babak Javanmard; Morteza Fallah karkan; Mohammadreza Razzaghi; Anahita Ansari Djafari; Saleh ghiasy; Behzad Lotfi; Reza Vafaee (Archives of Academic Emergency Medicine)
Introduction: Urogenital system injuries (UGIs) are seen in 10% of adult cases with multiple trauma. Although UGIs are rarely life threatening, they can cause major long-term morbidities. This study aimed to evaluate the characteristics of traumatic UGIs in patients who were referred to emergency department following multiple traumas.